2013
DOI: 10.3109/09593985.2013.868563
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation pulse duration and maximum tolerated muscle torque

Abstract: Neuromuscular electrical stimulation (NMES) is a physical therapy intervention used to treat muscle weakness. NMES-elicited forces during therapy are correlated with strength gains. Patient discomfort limits NMES-elicited forces potentially compromising strength gains and the efficacy of this invention. The purpose of this study was to determine if NMES containing two different electrical stimulation pulse durations (200 or 500 μs) affected the knee extensor muscle torques subjects tolerated. Other NMES charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Generally, longer phase durations generate greater muscle torque at least when monophasic square-wave pulses are used. [ 45 , 46 ] A recent study also showed that KFAC and PC, with the same phase duration, have similar efficiency for inducing %MVIC, and NMES with longer phase duration induces higher muscle-evoked torque regardless of the carrier frequency,[ 9 ] which indicates that phase duration plays an important role on muscle torque. Nevertheless, most of included studies used same phase (pulse) duration, which does not support the theory that KFAC had a short phase duration and produce less muscle torque compared to PC.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, longer phase durations generate greater muscle torque at least when monophasic square-wave pulses are used. [ 45 , 46 ] A recent study also showed that KFAC and PC, with the same phase duration, have similar efficiency for inducing %MVIC, and NMES with longer phase duration induces higher muscle-evoked torque regardless of the carrier frequency,[ 9 ] which indicates that phase duration plays an important role on muscle torque. Nevertheless, most of included studies used same phase (pulse) duration, which does not support the theory that KFAC had a short phase duration and produce less muscle torque compared to PC.…”
Section: Discussionmentioning
confidence: 99%
“…As stated previously, longer phase durations generate greater muscle torques, at least when monophasic square-wave pulses are used. 14,15 Phase duration and current amplitude determine the phase charge, which is responsible for muscle peripheral nerve recruitment. Therefore, the shorter phase duration of the BMAC may require that amplitude be increased to achieve the same phase charge, which may lead to greater discomfort and subsequently limit torque production.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Phase charge, the product of current amplitude and phase duration, 1,7,13 is an important parameter that determines stimulus strength and therefore motor nerve recruitment and torque production. 6,7,14,15 Phase charge can be increased by either increasing amplitude or phase duration, 13 and thus either high current amplitudes or longer pulse durations may facilitate greater muscle force production. However, this has only been shown with pulse durations up to approximately 500 to 600 microseconds; longer pulse durations have little effect on muscle force production.…”
Section: T T Conclusion: Neuromuscular Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, Hultman et al [2] demonstrated that increasing phase duration from 150 to 500 ms achieved a 40% greater torque output. In addition, when comparing low (200 ms) and high (500 ms) phase durations, healthy young individuals have been shown to tolerate and generate higher force tetanic muscle contractions (45% v 49% maximum voluntary contraction (MVC)) with a higher phase duration [63]. However, many HF-NMES applications use phase durations of <300 ms [3], despite the evidence supporting the use of higher phase durations for muscle strengthening applications.…”
Section: Pulse Durationmentioning
confidence: 99%